Gravitational waves from the birth of the universe with extended General Relativity - Bellini, Mauricio (2022)
During preinflation, the Hubble parameter increases from an initial null value and the expansion of the universe is produced by the effect of back-reaction effects. This fact is viewed in the global dynamics as a cosmological parameter which induces the initial expansion in a non-conservative General Relativity theory. In this framework, we study the production and evolution of primordial gravitational waves during preinflation using extended General Relativity with boundary terms included, that describe the sources of these waves.